The Role Of Creative Value Relationships "Teacher-Pupil" In The Development Of Students' Creative Skills (Eurasian Journal of Learning and Academic Teaching, 2023)
This article discusses the importance of developing the creative abilities of students based on interactive teaching methods and technologies. Works of a number of scientists about creativity. Opinions are presented on the assessment and development of practical skills and creative abilities of students using international experience.